Building a Lean Higher Education Model in Vietnam - Minh, Nguyen Dang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 3, 2018)
In recent years, Vietnam’s higher education sytem has been developing rapidly in scale and network with a vast extension in majors. What model Vietnam should apply in managing its higher education system is still a question that researchers and managers are encouraged to further work on. In this study, based on the Made in Vietnam Lean Management system, the author has studied and proposd a Lean Higher Education Model to be applied in managing the local higher education system in Vietnam. This model is expected to provide a new managerial approach that helps address the actual problems in university governance, and contributes to improving the operational effectiveness of the higher education institutions in Vietnam.